Assessment of Hearing Ability in Patients after Head and Neck Cancer Radiotherapy - Sohaila Yazdani; Kolsoum Teimouri; Negin Farshchian; Karim Khoshgard (Iranian Journal of Medical Physics)
Introduction: The study assesses radiation-induced sensorineural hearing loss (SNHL) in head and neck cancer patients, highlighting the common occurrence of SNHL as a significant side effect of radiation therapy (RT) targeting the cochlea and acoustic pathways. Material and Methods: The study included 34 patients (22 men, 12 women, mean age 40.13 ± 26.8 years) with head and neck cancers undergoing three-dimensional conformal radiation therapy (3D-CRT); 16 also had chemoradiotherapy (CRT). Pure-tone audiometry (PTA: 250-8000 Hz) was done before, immediately after, and three months post-RT for all patients. Hearing impairment was evaluated using the CTCAE 4.03 scoring system. Results: According to the findings, 19% and 37% of ears experienced SNHL immediately post-RT and 3 months after RT, respectively. The mean cochlear dose was 25.48 ± 13.56 Gy. A significant correlation existed between the cochlear dose and SNHL incidence (P-value < 0.05). Regression analysis indicated the mean cochlear dose as a robust predictor of SNHL, particularly at 8000 Hz (β = 0.570, P-value = 0.0001). Highest SNHL incidence at 8000 Hz, 3 months post-RT. A significant difference in SNHL threshold was observed between men and women at the frequency of 1000 Hz (P-value = 0.024). There was a statistically significant difference in SNHL thresholds between patients who underwent CRT versus those treated with RT alone (P-value < 0.05). Conclusion: RT commonly causes SNHL in head and neck cancer patients. Mean cochlear dose predicts SNHL, especially at higher frequencies.